Managing hospitality organizations achieving excellence in the guest experience - Ford, Robert C. (Robert Clayton) 1945-; Sturman, Michael C. (Michael Craig) (Thousand Oaks, California SAGE Publications, Inc., 2020)
"Today's economy is dominated by the service sector which continues to grow at a rapid pace. Even businesses dealing primarily psychical goods are now reinventing their image and positioning themselves as service providers. Introduction to Hospitality Management: Creating Excellent Guest Experiences 2e takes students on a journey through the unique world of the hospitality industry. Each chapter focuses on a core principle of hospitality management and is packed with practical advice, examples, and cases from some of the best companies in the service sector including Walt Disney, Southwest Airlines, and The Four Seasons. Authors Michael Sturman and Robert Ford emphasize the critical importance of focusing on your guest to create that unforgettable customer experience. Whether your students will be managing a neighborhood café, a convention center, or a high-end resort hotel, they will learn invaluable skills for managing services in today's ultracompetitive environment"--
The hospitality service strategy -- The basics of wow! the guest knows best -- Meeting guest expectations through planning -- Setting the scene for the guest experience -- Developing the hospitality culture: everyone serves! -- The hospitality service staff -- Staffing for service -- Training and developing employees to serve -- Serving with a smile: motivating exceptional service -- Involving the guest: the co-creation of value -- The hospitality service delivery system -- Communicating for service -- Planning the service delivery system -- Waiting for service -- Measuring and managing service delivery -- Fixing service failures -- Service excellence: leading the way to wow!
Previous edition: Managing quality service in hospitality : how organizations achieve excellence in the guest experience.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Customer services; Hospitality industry -- Management; Hospitality industry -- Personnel management